Relationship between dietary acid-base load and non-insulin-based resistance measures in patients with chronic kidney disease - Huang, Hui; Wang, Qian; Zhang, Ruimin; Liu, Fang; Niu, Yue; Luo, Yayong; Wang, Junqian; Li, Shuang; Tang, Zhengchun; Cao, Xueying; Wang, Xiaolong; Yang, Jian; et al. (Frontiers in Endocrinology, 2025)
This study explored the associations between triglyceride glucose (TyG), TyG with body mass index (TyG-BMI), triglyceride-to-high-density lipoprotein cholesterol (TG/HDL-C) ratio, and metabolic score for insulin resistance (METS-IR) and the effects of dietary acid-base load in patients with chronic kidney disease (CKD).MethodsA total of 288 patients with CKD were included in this study. Four non-insulin-based insulin resistance (IR) markers were used to assess IR levels in patients with CKD; dietary intake – 24-h dietary recall; and diet-based acidity – potential renal acid load (PRAL), net endogenous acid production (NEAP), and dietary acid load (DAL). Multiple linear regression analysis correlated dietary acid-base load and non-insulin-based IR markers.ResultsSpearman’s correlation indicated DAL was significantly associated with TyG-BMI (r = 0.251, P < 0.001) and METS-IR (r = 0.274, P < 0.001), but weakly correlated with the TG/HDL-C ratio (r = 0.14, P = 0.018). After adjusting for sex, age, energy, hypertension (HTN), diabetes, and estimated glomerular filtration rate, multiple linear regression analysis showed that DAL was associated with TyG-BMI (β = 0.336; P = 0.008) and METS-IR (β = 0.091; P = 0.007).ConclusionsPatients with the highest DAL scores had the highest TyG-BMI, TyG, TG/HDL-C ratio, and METS-IR. After adjusting for confounders, there was a significant positive association between DAL and TyG-BMI and METS-IR.